Institutional Space Of A Family In The South Of Russia: Specificity Of Traditions And Innovations - S. Chikaeva, Karina (2019)
The article provides a sociological analysis of traditional and innovative elements in the family sphere of the modern institutional space of the South Russian society. According to the results of our study, it was concluded that there is a negative attitude towards the institution of polygamy in the public consciousness of respondents. Moreover, there can be noted significant differences by gender: men, compared to women, are more positive about the institution of polygamy, despite the presence of negative assessments of this phenomenon.